Effect of a pparγ synthetic agonist associated with retinoic acid on 24-hour rhythms in the hippocampus of an experimental model of Alzheimer’s disease - Castro, A. (2021)
Alzheimer's disease (AD) is the most frequent cause of dementia in the older adults. The main pathogenic mechanism in sporadic AD is the decreasein amyloid beta peptide (Aβ) clearance. It is known that Apolipoprotein E (Apo E) modulates Aβ deposition and clearance. ApoE expression istranscriptionally induced by PPARγ in coordination with RXRs. Previously, we found that an intracerebroventricular injection of Aβ(1-42) modifiedthe daily rhythms of Apo E, Bmal 1, and Aβ in the rat hippocampus. Taking into account those observations, the objective of this work was toinvestigate the effects of synthetic PPARγ agonist, pioglitazone, and retinoic acid (Pio-RA) on the 24-h rhythms of Apo E, BMAL1 and Aβ proteinlevels, as well as on the daily rhythms of brain-derived neurotrophic factor (Bdnf) and its receptor (TrkB) expression in the rat hippocampus. In thisstudy, male Holtzman rats from control, Aβ-injected (Aβ) and Aβ-injected treated with Pio-RA groups were euthanized throughout a 24-h period andhippocampus samples were isolated every 6 h. Apo E, BMAL1 and Aβ proteins levels were analyzed by immunoblotting and Bdnf and TrkB mRNAlevels were determined by RT-PCR. Regulatory regions of Apo E and clock genes were scanned for E-box, RORE, RXRE and PPRE sites. Weobserved that the treatment of Pio-RA reestablished the daily rhythms of Apo E, Aβ, BMAL1 protein, and Bdnf mRNA levels. This treatment alsoincreased Bdnf and TrkB levels. We found E-box, RXRE, and PPRE sites on regulatory regions of Apo E and Bmal1 genes. The results of thepresent study could suggest that the treatment of Pio-RA would not only restore the altered rhythmic patterns of the clock genes and their target genesobserved in animals injected with Aβ aggregates, but also, interestingly, would increase the levels of cognition-related genes, which are decreased inAlzheimer's patients.